ROLE OF PERCUTANEOUS CT-GUIDED NEEDLE BIOPSY (PCNB) OF LUNG MASSES WITH IMAGING FEATURES AND HISTOLOGICAL CORRELATION - Dr Saumil desai; Dr Viraj shah; Dr Alpesh kalsariya (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
BACKGROUND• CT guided percutaneous needle biopsy of the lung is an indispensable tool in the evaluation of pulmonary abnormalities due to high diagnostic accuracy in the detection of malignancy.• Percutaneous biopsy in the lung plays a critical role in obtaining pathologic proof of malignancy, guiding, staging and planning treatment. MATERIAL AND METHODS• The study carried out is hospital based observational study in which 50 patients of all age group from 1st June to 31st December 2023 who were referred to the Department of Radiology in GCRI for further management were included in the study.• Imaging features of the lung masses were studied and reviewed with the literature. Histological examination was followed up and correlated with the imaging features of CT. RESULTS:• The study group was predominantly male (80 %) with highest incidence of lung masses in 51-60 years age group (40 %). Adenocarcinoma was most commonly affected (42 % of cases). CT findings included pleural effusion being most common pathology associated with lung masses. CONCLUSION• Percutaneous CT guided biopsy is an effective highly accurate and safe method of obtaining tissue for the diagnosis of indeterminate pulmonary lesions.